Peningkatan Pengetahuan dan Deteksi Dini Keputihan (Leukhorrea) pada Wanita Usia Subur di Desa Margorejo Pati - Sri Wahyuni (Institut Teknologi dan Bisnis Semarang, 2024)
Vaginal discharge is one of the reproductive health problems that often arise in adolescents which can be an early symptom of cervical cancer. Vaginal discharge is the discharge of white fluid or mucus that comes out of the genital organs that is not in the form of blood. Vaginal discharge is a complaint that often attacks women and does not know age (Sulistianingsih, 2014). Vaginal discharge is still considered not a serious thing so that in maintaining cleanliness, especially the genetic organs in women, are still lacking. This can be seen from the use of underwear that is not made of cotton. Even though it is possible that vaginal discharge can be caused by underwear made of synthetic fibers (nylon). (Kusmiran, 2019) The World Health Organization (WHO) in Suryandari and Rufaida (2019) stated that almost all women and adolescent girls have experienced vaginal discharge, 60% in adolescents (15-22 years old) and 40% in women (23-45 years old), if left vaginal discharge can cause adverse health effects, one of which is cervical cancer. Meanwhile, according to Wulandari (2015), as many as 75% of women who have experienced vaginal discharge at least 1 time in their lifetime with 50% in adolescents and 25% in women of childbearing age (WUS) out of 95% of cervical cancer cases that occur in women in Indonesia are characterized by vaginal discharge (3, 4). One of the effects of pathological vaginal discharge is cervical cancer. Every year, as many as 8,000 women in Indonesia die from cervical cancer. This means that almost every hour, an Indonesian woman dies because she is gnawed by cervical cancer. Cervical cancer attacks and kills women at the productive age of 20-25 years, but can appear in women at a younger age (5). Lack of proper knowledge and information about the health of the reproductive organs can cause a lack of attention to the health of the reproductive organs in terms of vaginal discharge.